Customer Satisfaction Analysis of ShopeeFood Service Quality using E-Servqual Method and Importance-Performance Analysis - Yanti, Rahma; Megawati, Megawati; Zarnelly, Zarnelly; Saputra, Eki; Marsal, Arif (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
ShopeeFood was launched in April 2020. However, since its initial release, traffic to ShopeeFood services did not immediately perform well, as the platform had to compete with major players like GoFood and GrabFood, which are already well-known among the public. Numerous negative customer reviews about ShopeeFood indicate that customer satisfaction with the company's performance remains low. To measure the level of customer satisfaction, this study employed the E-Service Quality (E-Servqual) and Importance-Performance Analysis (IPA) methods. The results of the study show that, on average, the seven dimensions of E-Servqual measured exhibit a gap, with the average gap being negative. The highest gap was found in the